Information, Price, and Barriers to Adoption and Usage of Mobile Money : Evidence from a Field Experiment in the Gambia - Cruces, Guillermo Antonio (2020)
Mobile money has been heralded as a way to foster financial inclusion. While it has become popular in developing countries, most notably in African nations, there are still strong barriers to its adoption and usage. The purpose of this study is to examine the extent to which a lack of information and high prices are limiting factors in the adoption of mobile money. We implemented a simple randomized controlled trial among a group of difficult-to- access potential users: mobile phone users in The Gambia who had opened mobile money wallets but had not made a transaction. We offered meaningful price discounts on withdrawal charges, and made these discounts salient by reminding users about them every month for a period of six months. Our analysis measures different dimensions of mobile money use by drawing from administrative mobile phone company records. We also carried out a post- treatment survey to gauge knowledge about, and attitudes towards, mobile money. Our results indicate that treated individuals were substantially more aware than controls about the uses of mobile wallets and about the meaningful discounts of 15% and 30% offered. However, only a small fraction of treated individuals started using mobile wallets, and the difference was not statistically significant. Perceptions of safety, trust in the platform, and service reliability were not significantly different between treated and controls. However, treated individuals were more likely to perceive the service charges to be expensive. We interpret this as evidence that our population of interest was uninformed about the platform at large. While our treatment increased awareness about its capabilities and operation, potentially fostering its adoption, it also increased awareness of the relatively high fees it involves, which in turn limited usage. Both a lack of information and high prices need to be addressed to foster the adoption and usage of mobile money in developing countries.